2018
DOI: 10.4103/ijnmr.ijnmr_65_17
|View full text |Cite
|
Sign up to set email alerts
|

Association between Outcome of severe traumatic brain injury and demographic, clinical, injury-related variables of patients

Abstract: Background:Traumatic brain injury (TBI) is a main health problem among communities. There exists a variety of effective factors on the outcome of patients with TBI. We describe the demographic, clinical, and injury related variables of the patients with severe TBI, and determine the predictors of outcome.Materials and Methods:We did this cross-sectional study on all 267 adult patients with severe TBI admitted to three trauma centers of Isfahan University of Medical Sciences (IUMS) from March 20, 2014 to March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…(8,12,25) Interestingly, the other study conducted on TBI in Iranians reported that its subjects were 85% men and 15% women, figures that are identical to the gender ratio of our patients. (3) However, our comparison of clinical outcomes of TBI shows that gender has no effect on the incidence of death following a TBI. Considering that several other studies have reported a similar conclusion, (3,7,26) it can be claimed with sufficient confidence that gender has no impact on the outcome of TBI.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…(8,12,25) Interestingly, the other study conducted on TBI in Iranians reported that its subjects were 85% men and 15% women, figures that are identical to the gender ratio of our patients. (3) However, our comparison of clinical outcomes of TBI shows that gender has no effect on the incidence of death following a TBI. Considering that several other studies have reported a similar conclusion, (3,7,26) it can be claimed with sufficient confidence that gender has no impact on the outcome of TBI.…”
Section: Discussionmentioning
confidence: 80%
“…Flow diagram of traumatic brain injury similar reports in other studies suggests that age is likely to be a key factor of the clinical outcome of TBI, and younger people have a lower chance of mortality following a TBI. (3,10) It has also been reported that each year of increase in age is associated with 5% higher chance of postconcussion syndrome and 2% higher chance of a GCS of less than 7. (10,18,19) Both quantitative and qualitative analyses of our study showed that reduced GCS is another important factor in the adverse clinical outcomes of TBI.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations